Quantification of the effectivity of laser therapy shortly following brain injury via dual-wavelength laser imaging. (January 2022) - Shemesh, David; Aburus, Ohad; Turgeman, Gadi; Abookasis, David
Highlights: The effect of laser irradiation immediately after brain injury was study. Dual-wavelength laser speckle imaging was employed to monitor changes in tissue properties. Tissue temperature was imaged by a thermal camera providing additional information on tissue condition. Laser irradiation found to inhibit the development of complications over the injured area. Different doses of low-level laser irradiation were also tested with less effectiveness on parameters. Abstract: Treatment of traumatic brain injury, within a few minutes and even before transportation to the nearest medical facility, can significantly curtail injury severity and even prevent death. The primary aim of this study was to evaluate the effect of laser irradiation as a therapeutic intervention tool immediately following brain injury. To this end, a dual-wavelength laser speckle contrast imaging (DW-LSCI) system based on two laser sources at two wavelengths 532 and 660 nm was employed to monitor changes in cerebral blood flow, tissue saturation and rate of oxygen consumption in a mouse model of intact head injury. In addition, structural changes of tissue were evaluated using linear approximation to Rayleigh-MIE scattering in the range between the two laser wavelengths. Furthermore, cerebral tissue temperature was imaged by a thermal camera providing additional information on physiological brain tissue condition. Experiments were conducted on anesthetized mice ( n = 6, female) subjected to a closed head weight-drop model of focal brain injury. After 5 min of baseline measurement, focal brain injury was induced and measurements were conducted for 10 min. Low-level laser therapy (LLLT) was than administrated for a duration of 15 min with uniform exposure of 45 J/cm 2 from a CW diode laser source (810 nm). Concurrently, measurements were carried out over the treatment time interval. Laser illumination was then blocked and measurements continued for another 20 min, followed by euthanasia. In comparison to baseline measurements, noticeable variations were revealed post-injury which indicate the severity of brain damage. The use of LLLT inhibited the development of complications in the injured mice by increasing blood flow and saturation and overall oxygen consumption level over the injured area which highlights its effectiveness as a neuroprotective agent immediately following brain injury. Different doses of low-level laser irradiation were also tested ( n = 12) with less effectiveness on cerebral parameters. The results presented here support our hypothesis that a high dose of laser irradiation as a first aid can attenuate the injury and save the brain from further worse outcome. To the best of our knowledge, the implementation of the DW-LSCI system to monitor brain hemodynamic and metabolic response to LLLT shortly after head injury in intact mouse brain has not been previously reported.